PROCEDIMENTO ALTERNATIVO PARA DETERMINAÇÃO DE METAIS EM BIODIESEL POR ESPECTROMETRIA DE ABSORÇÃO ATÔMICA USANDO DIGESTÃO EM MICROONDAS - Pinto, Raimunda Anésia Araújo (2010)
Thinking of the metals sodium, potassium, calcium and magnesium can damage the stability of biodiesel, because they tend to react with esters and to produce soap, this work aimed to carry out a procedure for determination of metals in biodiesel of different matrices by flame atomic absorption spectrometry (F-AAS) using the sample preparation procedure in microwave. For the digestion process, we used the procedure suggested by the equipment for digestion of samples of biodiesel, noting the most important variables in this procedure, such as; time of maximum power, volume of reagents and sample. The levels of sodium, potassium, calcium and magnesium in soybean biodiesel, for instance, were 2925.00 ± 527.89; 164.45 ± 28.27; 306.58± 42.98 e 26.95 ± 3.92 mg Kg-1, respectively. The digestion method proposed was adequate for the preparation of biodiesel samples from different matrices and can be applied for determination of these metals by F-AAS. The method validation was obtained by comparing the method proposed in this work and a procedure that uses sample digestion in microwave oven to determine these metals by ICP-OES. The results obtained by the proposed method were in agreement with results obtained by the proposed method, thereby, the new method is an efficient alternative for the determination of metals in biodiesel, in addition to supplying the deficiencies presented by the method of dilution with solvent.